REVITALIZING HISTORICAL TOURISM DESTINATION THROUGH GAMIFICATION AND STORYTELLING: A CASE STUDY OF THE WARUNGBOTO SITE IN YOGYAKARTA - Bonifasia Yuniar Rifani; Asti Ayuningsih (Kepariwisataan: Jurnal Ilmiah, 2025)
AbstractThis study examines the potential development of gamification and storytelling in revitalizing historical tourism destinations at the Warungboto Site, Yogyakarta. The research aims to develop a concept for historical site development by integrating digital technology and gaming elements to enhance tourist experiences. Through analyzing the site's strengths in natural, historical, and spiritual aspects, the "Rediscover The Lost Garden" concept was developed to facilitate site exploration and interpretation through interactive games and puzzles. The research employed a qualitative approach with case study design, involving data collection through historical literature review, field observations, and in-depth interviews with 12 key informants. The findings identified three main site strengths that can be optimized through gamification: (1) natural elements comprising springs and historical gardens, (2) historical value from the era of Sultan Hamengku Buwono II, and (3) spiritual aspects reflected in the building's architecture and functions. The gamification implementation is designed across four exploration zones with progressive difficulty levels, utilizing augmented reality technology to digitally reconstruct site conditions. A reward system based on points and virtual badges is implemented to encourage comprehensive exploration. This research contributes to the development of a gamification model for historical tourism destinations that integrates digital technology while preserving heritage values.Keywords: Gamification; Heritage Tourism; Augmented Reality in Tourism; Digital Story Telling; Situs WarungbotoAbstrakPenelitian ini mengkaji potensi pengembangan gamifikasi dan storytelling dalam merevitalisasi destinasi wisata sejarah di Situs Warungboto, Yogyakarta. Studi ini bertujuan untuk mengembangkan konsep pengembangan situs sejarah dengan mengintegrasikan teknologi digital dan permainan untuk meningkatkan pengalaman wisatawan. Melalui analisis kekuatan situs dalam aspek alam, sejarah, dan spiritualitas, konsep "Rediscover The Lost Garden" dikembangkan untuk memfasilitasi eksplorasi dan interpretasi situs melalui permainan dan teka-teki interaktif. Penelitian menggunakan pendekatan kualitatif dengan studi kasus, melibatkan pengumpulan data melalui tinjauan literatur sejarah, observasi lapangan, dan wawancara mendalam dengan 12 informan kunci. Hasil penelitian mengidentifikasi tiga kekuatan utama situs yang dapat dioptimalkan melalui gamifikasi: (1) elemen alam berupa mata air dan taman bersejarah, (2) nilai sejarah dari era Sultan Hamengku Buwono II, dan (3) aspek spiritualitas yang tercermin dalam arsitektur dan fungsi bangunan. Implementasi gamifikasi dirancang dalam empat zona eksplorasi dengan tingkat kesulitan bertahap, menggunakan teknologi augmented reality untuk merekonstruksi kondisi situs secara digital. Sistem penghargaan berbasis poin dan lencana virtual diterapkan untuk mendorong eksplorasi menyeluruh. Penelitian ini berkontribusi pada pengembangan model gamifikasi destinasi wisata sejarah yang mengintegrasikan teknologi digital dengan tetap mempertahankan nilai-nilai sejarah.Kata Kunci: Gamifikasi; Wisata Sejarah; Augmented Reality dalam Pariwisata; Digital Storytelling; Situs Warungboto